Impact of the Covid-19 coronavirus disease pandemic on Slovene organisations and institutions in the Raba region - Munda Hirnök, Katalin (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
The article provides an analysis of the activities of Slovene organisations and institutions in the Raba Region during the first wave of the Covid-19 epidemic. Initially, the author points to the vulnerability of the Slovene national community, which is closely related to historical circumstances. The study of articles published in electronic media and the analysis of the results of online surveys and semi-structured interviews with Slovene minority organisations and institutions in the Raba Region suggest that the Slovene national community adapted to the new normality and coped with the challenges brought by the epidemic relatively well. The closure of border crossings between the Raba Region and Goričko cut cross-border contacts, thus affecting the Slovene minority in all areas of life and stirring discomfort and criticism among the Slovenes from the Raba Region. Due to the unpredictable course of the Covid-19 epidemic, it is not yet possible to anticipate any long-term consequences thereof for the activity of Slovene organisations in the Raba Region.
Keywords: Madžarska; pandemija covid 19; Porabje; porabski Slovenci; Slovenija; slovenska manjšina; slovensko-madžarsko obmejno območje